2020
DOI: 10.1097/jcma.0000000000000188
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of treatment results and prognostic factors of uterine sarcoma: A single-center experience

Abstract: Background: Uterine sarcomas (US) constitute a rare heterogeneous group of gynecological malignancies with aggressive characteristics and poor prognosis. Identifying the histopathological factors that determine the prognosis of the tumor and efficacy of various treatment modalities provides a reliable source for efficient treatment of affected patients. This study presents our 11-year experience with US in the south of Iran. Methods: Medical records of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 25 publications
2
5
0
1
Order By: Relevance
“…The univariate analysis showed that over 50 years, post-menopause, advanced stage, and ≥1/2 myometrial invasion were signi cantly associated with poorer survival; while multivariable analysis demonstrated that post-menopause and advanced stage were independent prognostic factors for survival of the total cohort and the LMS group. These ndings were consistent with previous studies showing higher incidence and poorer prognosis of uterine sarcoma in postmenopausal women, women aged >50 [19,20] and with advanced tumor stages [14,21]. Our study showed that the 5-year survival rate of ESS was as high as 84.9%, which was similar to the reported survival rate of 75% in an Iran study with 42 patients [21].…”
Section: Discussionsupporting
confidence: 93%
“…The univariate analysis showed that over 50 years, post-menopause, advanced stage, and ≥1/2 myometrial invasion were signi cantly associated with poorer survival; while multivariable analysis demonstrated that post-menopause and advanced stage were independent prognostic factors for survival of the total cohort and the LMS group. These ndings were consistent with previous studies showing higher incidence and poorer prognosis of uterine sarcoma in postmenopausal women, women aged >50 [19,20] and with advanced tumor stages [14,21]. Our study showed that the 5-year survival rate of ESS was as high as 84.9%, which was similar to the reported survival rate of 75% in an Iran study with 42 patients [21].…”
Section: Discussionsupporting
confidence: 93%
“…13 Longest survival was reported for ESS and shortest for carcinosarcoma in a retrospective study on 42 patients. 11 Older age, advanced stage, presence of necrosis, and high mitotic index increased the hazard ratio of mortality. 11 From the results of our study, the median survival of patients with LGESS, LMS, HGESS, UES, AS, and STUMP were 32, 11, 4, 9.5, 26, and 42 months, respectively, and the median DFS for the entire cohort of uterine sarcoma was 32 months, and the median OS was 57 months.…”
Section: Discussionmentioning
confidence: 98%
“…11 Older age, advanced stage, presence of necrosis, and high mitotic index increased the hazard ratio of mortality. 11 From the results of our study, the median survival of patients with LGESS, LMS, HGESS, UES, AS, and STUMP were 32, 11, 4, 9.5, 26, and 42 months, respectively, and the median DFS for the entire cohort of uterine sarcoma was 32 months, and the median OS was 57 months. The better survival in this study may be attributed to the following reasons: Patients diagnosed with carcinosarcoma were excluded, most of the patients were managed in early stages, and LGESS was the most common histological type encountered which naturally had a better prognosis when compared to other histological subtypes.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Os LM são comumente tratados com medicamentos hormonais, anti-inflamatórios e suplemento de vitaminas e ferro por conta dos nutrientes perdidos no sangramento (Hajhashemi et al, 2019;Bradley et al, 2019;Archer et al, 2017). Já os LMS, a principal opção terapêutica é a remoção uterina seguida por terapia adjuvante como radioterapia ou quimioterapia, com o objetivo de evitar recidiva e metástase (Momtahan et al, 2019). Tendo em vista as alternativas oferecidas até o presente momento, estudos que possibilitem a identificação de novas opções terapêuticas para ambos tumores, apresentam efeito benéfico para as pacientes.…”
Section: Introductionunclassified